HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK SISWA PUTRI KELAS VIII SMPN 1 SIAK KECIL - Khaerman, Khaerman; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, type of research is correlational research that collected two variables x and y variables. As the variable x is the explosive power leg muscle class VIII SMPN 1 Siak Kecil and a variable y is the result of long jump squat style female student of class VIII SMPN 1 Siak Kecil. The population in this study were female student class VIII SMPN 1 Siak Kecil, amounting to 32 people consisting of 7 boys and 25 female student. The sample in this study specifically taking a class VIII student daughter SMPN1 Siak Kecil, amounting to 25 people. Researchers took samples of students with daughter on the grounds that the data research homogeneous. From the calculation of correlation values can be seen that the large value of the relationship between the explosive power leg muscle with the results of the long jump squat style female student of class VIII SMPN 1 Siak Kecil is 0.415 with rtabel value = 0.396, it means rhitung = 0.415> rtabel = 0.396 and it can be said that there is a relationship between the explosive power leg muscle with the results of the long jump squat style female student of class VIII SMPN 1 Siak Kecil. Ho hypothesis testing criteria accepted if thitung smaller than ttabel while the calculation results show that t = 2:19> table = 1.714, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that